ГЕНЕЗИС ЭТНИЧЕСКИХ ПРОТИВОРЕЧИЙ В РЕСПУБЛИКЕ МАКЕДОНИЯ: (албанско-македонский аспект) (Philological Studies, 2019)
Republic of Macedonia (FYROM) is one of the Balkan states. Macedonians, Albanians and other nationalities inhabit this territory. For a long period of time the Albanians were fighting (from the political disputes to open conflicts) for their recognition as a state-nation. The Armed Conflict 2001 brought the country to the brink of civil war, but the actions of politicians contributed to the signing of the Ohrid framework agreement. This paper changed the life of the state, but did not solve the problems between Albanians and Macedonians in Macedonia.
Keywords: Republic of Macedonia, FYROM, the conflict in 2001, the Ohrid agreement, the Framework Agreement, Albanians, Macedonians